2021
DOI: 10.3389/fcell.2021.713254
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of RP105 in Regulation of Inflammation and Osteoclastogenesis During Inflammatory Diseases

Abstract: Inflammatory diseases have a negative impact on bone homeostasis via exacerbated local and systemic inflammation. Bone resorbing osteoclasts are mainly derived from hematopoietic precursors and bone marrow monocytes. Induced osteoclastogenesis during inflammation, autoimmunity, metabolic diseases, and cancers is associated with bone loss and osteoporosis. Proinflammatory cytokines, pathogen-associated molecular patterns, or endogenous pathogenic factors induce osteoclastogenic differentiation by binding to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 206 publications
0
2
0
Order By: Relevance
“…TLRs play an important role in the pathophysiology of infection and inflammatory diseases 38 . Although CD180 is a nonclassical member of the TLR family, it is the most common TLR on cell surfaces 39 . We found that CD180 was highly expressed in ALI tissues; however, the difference was not significant in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs play an important role in the pathophysiology of infection and inflammatory diseases 38 . Although CD180 is a nonclassical member of the TLR family, it is the most common TLR on cell surfaces 39 . We found that CD180 was highly expressed in ALI tissues; however, the difference was not significant in the validation set.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the bone remodeling process can result in abnormal bone structure and function, thereby leading to a variety of skeletal disorders . Several inflammatory musculoskeletal disorders in adults, such as periodontitis, rheumatoid arthritis, osteoarthritis, and peri-implantitis, are associated with the loss of bone mass due to excessive OC activity. , Numerous studies have adopted the strategy of OC differentiation inhibition to alleviate these pathological disorders.…”
Section: Introductionmentioning
confidence: 99%